Purchase or Lease of All-Purpose Vehicles for Government Offices - Philippine Institute for Development Studies (PIDS) (Philippine Institute for Development Studies (PIDS), 2014)
This article compares the costs and benefits for the government of leasing vis-a-vis outright purchase of motor vehicles. It presents two methods through which public managers can estimate and assess the value of procuring motor vehicles either under lease payment or direct purchase. Using data from selected government agencies, the net present values generated suggest that outright purchase of low-end vehicles is preferable to leasing. For high-end models, leasing offers a more practical option. The findings, however, are far from conclusive because assumptions regarding the variables and input data are subject to change. Results can be significantly improved with better and more accurate statistics. To gain sufficient understanding of the issue, factors other than those covered by the study, i.e., economies of scale and entry of commercial banks, must also be explored.
Keywords: 330; government procurement; Philippines; zero-based budgeting; all-purpose vehicles; lease payment; motor vehicle acquisition; direct purchase